Supply Chain Management as a Resource for Innovative Development - Irina B. Yulenkova; Aleksey A. Natalin (International Journal of Supply Chain Management, 2020)
Abstract—In modern economic conditions, innovation is a prerequisite that can ensure competitiveness in the long term. Intellectual resources are the crucial factor in the innovative development of the economy, which determines the relevance of studying supply chain management and the processes associated with it. The goal of this research was to assess the prospects for innovative development in the Republic of Mordovia. For this purpose the authors analyzed the theoretical and methodological aspects of supply chain management formation and explored the scenario-based approach that allows identification and assessment of possible risks when developing a regional policy. The subject matter of the study was the scientific, technological, and innovative development of the region on the example of the Republic of Mordovia. The authors applied factor and system analysis, expert survey, planning, forecasting, and a comparative method. The research was carried out using the data of Rosstat, Rospatent, and Mordoviastat. The authors determined the specifics of the supply chain management development in the region. In addition to this, the authors applied the scenario approach to analyze the current conditions in fundamental and applied science, the infrastructure of scientific, technical, and innovative activities, which allowed assessing the possible risks in the development of regional policies. The article proposed a long-term forecast for the development of science in the Republic of Mordovia. The assessment of the scientific and technological development of the region with a focus on intellectual potential allowed forecasting the impact of supply chain management on innovative development and sustainable economic growth. The research results can be used in the development of strategies and tactics of the regional policy.